ANALISIS GAYA BELAJAR SISWA DALAM PEMBELAJARAN BIOLOGI DI KELAS X IPA SMA NEGERI 7 PADANGSIDIMPUAN - Romaito Simatupang (PRODI PENDIDIKAN BIOLOGI, 2019)
This study aims to describe students’ learning style and the factors that influence it in biology teaching learning process at the tenth grade students of SMA Negeri 7 Padangsidimpuan. The research was conducted by applying descriptive qualitative for 3 months (April-June 2018). The informants of the research were the tenth grade students of IPA -2 (23 students). Questionnaires, interview, and documentation were used in collecting the data. The result showed: (1) students’ learning visual style was 56.53% (13 students), (2) students’ learning auditory style was 30.43% (7 students), and (3) students’ learning kinesthetic style was 13.04% (3 students). The influence of students learning were (1) internal factors which include intelligence, interest, motivation, and (2) external factors which include school environment.